Non-interpersonal traumatic events in patients with eating disorders: a systematic review - Johnsen, Kirstine Marie; Nielsen, Kirstine Franciska; Nilsson, Kristine Kahr; Kjaersdam Telléus, Gry (Frontiers in Psychology, 2024)
Objectives The purpose of the systematic review was to synthesize literature on eating disorders (ED) and non-interpersonal traumatic events (NTE) and consolidate the reported prevalence of NTE in patients with an ED. Methods The literature search was performed in Embase, PsycInfo, and PubMed. The keywords in the search were “eating disorder,” “trauma” and “non-interpersonal,” using index-terms and free-search keywords related to NTE and ED. The PRISMA guidelines were followed. Relevant studies were screened using Rayyan. Results Of the 16 studies included in the quantitative synthesis, five overall types of NTE were identified: accidents, illness, injury, natural disaster and war. Findings provided tentative evidence for illness and injury being more prevalent in patients suffering from an ED compared to controls. The remaining subtypes of NTE did not show a higher prevalence in patients with an ED when compared to controls. Findings also suggest that those with binge/purge subtype of anorexia nervosa (AN) had a higher prevalence of non-interpersonal traumatic events compared to the restrictive subtype of AN. Discussion This systematic review provided a clear synthesis of previous findings related to NTE among patients with an ED. Noteworthy, is that many studies do not take into account if the trauma happened prior or after to ED onset, which may affect the association. Furthermore, the body of research on NTE in patients with ED is exceedingly limited, and more research is needed.